"WBC over DVB-H" Testbed Design, Development and Results. (28th January 2010) - Ji Ji, Zhanlin Zhanlin; Ganchev Ganchev, Ivan Ivan; O'Droma O'Droma, Máirtín Máirtín
Abstract : The wireless billboard channels (WBCs) are integral part of the ubiquitous consumer wireless world (UCWW)—a wireless next generation network proposal. The WBCs are used by the service providers to broadcast advertisements of their (wireless) services to the mobile terminals so that the mobile users may discover and associate with the "best" services following the user-driven ''always best connected and best served'' paradigm. A three-layer system architecture of WBCs established over the digital video broadcasting-handheld (DVB-H) standard is presented. The design and development of a corresponding ''WBC over DVB-H'' experimental testbed are described. Various results obtained from the testbed are presented and explained.